Matter – a current picture. (1st May 2017) - Macrae, Roderick
A century ago, a two-part review by W. C. McC. Lewis entitled "The Structure of Matter" appeared in this journal, surveying the achievements that had been made to date in that field. Topics included the value of Avogadro's constant, the dimensions of a molecule, equations of state for non-ideal gases, then-current theories relating electron configurations to the Periodic Law, the then-new nuclear atom model of Rutherford, and the first findings from X-ray crystallographic studies of matter, a field then in its nascent phase. This article is a sequel to that work. As a vast quantity of research has been addressed to the topic in the intervening period, the view presented here can at best be selective and idiosyncratic. Nonetheless, it attempts to capture some of the important strides in 'matter science', broadly defined, over the past century, highlight some recent areas of interest or novelty, and give a picture of some of the mysteries that remain.